2023
DOI: 10.1038/s41467-023-37992-x
|View full text |Cite
|
Sign up to set email alerts
|

Isthmin-1 (Ism1) modulates renal branching morphogenesis and mesenchyme condensation during early kidney development

Abstract: The outgrowth of epithelial bud followed by reiterated bifurcations during renal development is driven by the ligand-receptor interactions between the epithelium and the surrounding mesenchyme. Here, by exploring ligand-receptor interactions in E10.5 and E11.5 kidneys by single cell RNA-seq, we find that Isthmin1 (Ism1), a secreted protein, resembles Gdnf expression and modulates kidney branching morphogenesis. Mice deficient for Ism1 exhibit defective ureteric bud bifurcation and impaired metanephric mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Gao et al found that Ism-1 plays a critical role in early kidney development. Ism-1 knockout mice failed in branching morphogenesis and mesenchyme condensation 30. Both podocyte impair and tubulointerstitial changes are important in DKD development 31 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al found that Ism-1 plays a critical role in early kidney development. Ism-1 knockout mice failed in branching morphogenesis and mesenchyme condensation 30. Both podocyte impair and tubulointerstitial changes are important in DKD development 31 32.…”
Section: Discussionmentioning
confidence: 99%
“…Ism-1 knockout mice failed in branching morphogenesis and mesenchyme condensation. 30 Both podocyte impair and tubulointerstitial changes are important in DKD development. 31 32 Further mechanistic studies are required to elucidate the relationship between Ism-1 and impaired kidney function.…”
Section: Discussionmentioning
confidence: 99%